2020
DOI: 10.1186/s12913-020-05188-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the youth-friendliness of youth clinics in northern Sweden: a survey analyzing the perspective of the youth

Abstract: Background: Sweden has nearly 300 youth clinics that have been offering services since the 1970s. However, no evaluation has been done to assess their youth-friendliness. This study aims to assess: i) to what extent youth clinics are perceived as youth-friendly by the young people using them; and ii) if the level of youth friendliness is equally perceived across different sociodemographic groups of users. Methods: The four northernmost counties of Sweden were included in the study. Of the total identified 22 y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
(37 reference statements)
3
8
0
Order By: Relevance
“…Although previous research has shown that YCs in northern Sweden are youth-friendly [19,20] no qualitative studies have looked in-depth at how Swedish youth perceive YFHS and in particular the 'youth friendliness' of these services. Knowledge about young people's specific needs and preferences and how they seek and receive help is crucial for ensuring that the right information and services are provided.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has shown that YCs in northern Sweden are youth-friendly [19,20] no qualitative studies have looked in-depth at how Swedish youth perceive YFHS and in particular the 'youth friendliness' of these services. Knowledge about young people's specific needs and preferences and how they seek and receive help is crucial for ensuring that the right information and services are provided.…”
Section: Introductionmentioning
confidence: 99%
“…To a large extent, both youth clinic staff and visitors regard Swedish youth clinics to be youth-friendly as defined by the WHO, that is, accessible, acceptable, equitable, appropriate, and effective for different youth sub-populations [102,105]. The young people's perception of youth friendliness was favourable regardless of gender.…”
Section: Swedish Youth Clinicsmentioning
confidence: 99%
“…The young people's perception of youth friendliness was favourable regardless of gender. However, younger visitors; users who did not categorize themselves as either heterosexual, homosexual, or bisexual; users with trans experiences; and users with non-Swedish backgrounds gave youth clinics lower scores for certain domains [105]. The professionals also acknowledged challenges regarding equitable access to different youth sub-populations.…”
Section: Swedish Youth Clinicsmentioning
confidence: 99%
“…Sweden has provided around 300 YCs, which have been working since the 1970s to respond to the healthcare needs of young people. According to a survey among young people using YCs in northern Sweden, YCs were rated highly in relation to several aspects of youth-friendliness such as accessibility, equity, respect, privacy and confidentiality, no judgement, and quality [ 24 ]. When it comes to offering first-line mental healthcare to young people, YCs have several advantages over other services – they are widespread, many employ professionals with expertise in mental (ill) health and, most importantly, they are trusted by young people [ 2 ].…”
Section: Introductionmentioning
confidence: 99%